PENGARUH BIAYA MAINTENANCE TERHADAP LABA PERUSAHAAN - Manurung, Elizabeth Tiur Manurung; Meta Aulia Rizqi; Angela Novita Sutanto; Adriano, Mayang Gitakusumah (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This research aim is to investigate the influence of maintenance costs on company profits in the context of manufacturing industry. The study is conducted on companies operating in food and beverage production sector, specifically PT Mayora Indah Tbk. Quantitative descriptive analysis method is used to examine this research, with maintenance costs as independent variable and net profit as the dependent variable. The result shows a significant positive regression between maintenance costs and net profits. Investing in good maintenance can enhance operational safety and product quality, positively influence long-term profits , and improve the company's reputation, and. Therefore, the manager must take the maintenance costs into account when calculating the company's expenses, because maintenance costs significantly affect on the company's profit. This research utilizes the latest data from company financial reports for the period 2016-2024, which was not available in previous studies, thereby providing more up-to-date insights into the relationship between maintenance costs and company profits.